The effect of Punica granatum L. flower extract on post-surgical peritoneal adhesions in a rat model. (March 2020) - Mahmoudieh, Mohsen; Keleidari, Behrouz; Nasr Esfahani, Farid; Zolfaghari, Behzad; Melali, Hamid; Davarpanah Jazi, Amir Hosein; Mehdinezhad, Negin; Mokhtari, Mojgan
Abstract: Objective: Peritoneal adhesions may develop after every abdominopelvic surgery. Many agents and technical modifications have been investigated to minimize adhesions. Punica granatum (pomegranate) flower has some anti-inflammatory and antioxidative effects that would reduce the formation of peritoneal adhesions. In the present study, the effects of different doses of oral Punica granatum flower extract on postoperative peritoneal adhesions were evaluated in a rat model. Study design: Thirty-two female Wistar rats were divided into four groups: one control group (CG) and three experimental groups, treated with 100 (EG100), 200 (EG200), and 400 (EG400) mg/kg/day Punica granatum extract orally for eight days. Induction of peritoneal adhesions was done in all groups using the same method. Two weeks after the first surgery, all rats re-operated and adhesions were evaluated via both macroscopic and microscopic changes. Results: We observed that rats in the control group had statistically higher adhesion area and more severe adhesions when compared to all experimental groups. Besides, those in the EG-400 group had a significantly lower rate of foreign body reaction in serosal layer when compared to the other three study groups. Other microscopic findings were comparable between the four groups. Conclusion: Administration of the oral Punica granatum flower extract was associated with a decreased quantity and quality of the adhesions in the animal model of rat in this study. This therapy might be an effective and safe strategy to reduce intraperitoneal adhesion after abdominal surgeries in animal models.